Improving Public Investment Efficiency in the G-20. (Policy Papers; Policy Paper, 2015)
Through the provision of both social and economic infrastructure, public investment can serve as an important catalyst for economic growth. A significant body of theoretical and empirical research underscores the positive relationship between investment in high-quality public infrastructure and economy-wide productivity.1 Against the background of a steady decline in public investment as a share of GDP in advanced economies, evidence of infrastructure bottlenecks in emerging economies, and the sluggish global economic recovery, the G-20 has called for ramping up public investment to raise long-run economic growth (G-20, 2014).2 However, the economic and social impact of public investment crucially depends on its efficiency. Despite anecdotal evidence of projects plagued by time delays, cost overruns, and inadequate maintenance, there are few robust empirical studies of the determinants of public investment efficiency. This paper explores the link between public investment management (PIM) institutions and the efficiency of public investment for the G-20 countries. Based on the analysis from a recent IMF study, the paper finds that better PIM enhances public infrastructure quality, and pinpoints key institutional reforms needs to boost public investment efficiency (IMF 2015). These findings and recommendations are based on a comprehensive data set on investment, infrastructure and capital stocks, and two analytical innovations: (i) a new cross-country Public Investment Efficiency Index (PIE-X); and (ii) a new Public Investment Management Assessment (PIMA) which is applied to G-20 countries.